APLIKASI TEORI POLITIK ISLAM PERSPEKTIF KAIDAH-KAIDAH FIKIH - Hasan, Mustofa (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2014)
In Islamic politics(fiqh al-siyâsah), one of the material studies is a power. In brief, the Islamic politics includes constitutional law,administrative law, international law, and economic law. In view of the relation, on the other hand, it discusseson the relationship of people and the leader as a concrete ruler in a country, inter-nation, or in their national andinternational economic policy. In Islamic politics, there are many theories formulated by some moslem scholarsthat become guide in a practice. Besides, this Islamic jurisprudence theory, as its real advantage, will gather theproblems that have same reason. This theory also will make easy to social life in political activities. This article isaimed at describing 12 Islamic legal norms which relevantly should be applied now and in the future.